JOB DEMANDS TERHADAP WORK ENGAGEMENT PADA KARYAWAN DI PT X - Desi Natalia; ,Sutarto Wijono (Bajang Institute, 2023)
This research aims to determine the effect of job demands on work engagement in employees at PT X. This study uses the quantitative method. The subjects in this study amounted to 53 people, using saturated sampling techniques. The measuring tool used uses Rahyu's (2019) job demands scale and I Gde Dhika Widarnandana's (2019) work engagement. These two variables refer to the theories of Schaufeli and Bakker (2004). Data collection procedure by distributing questionnaires online using googleform. In analyzing the data, researchers used SPSS Version 25.0. The results showed that there was a significant influence between job demands on work engagement in employees at PT X.